KESALAHAN LOGIKA DALAM PEMBELAJARAN BAHASA INDONESIA PEMELAJAR JEPANG BIPA TINGKAT A1 - Faridah Suciyatmi (BASA Journal of Language & Literature, 2022)
This study aims to describe syntactic level errors in the essays of seventh grade students of SMP PGRI 1 Kediri in the use of sentences. This research uses a qualitative approach with a descriptive research type. The study in this research was conducted in depth and in detail to obtain a clear description of the errors in the use of sentences in the syntactic level in students' essay writing. In this study, data were collected through reading, recording, and interviewing teachers and students. The data collection procedure consists of the preparation stage, data collection, data analysis, and presentation of data analysis results. Data analysis techniques include identification, categorization, data presentation, and conclusion drawing. The results of this study show that students make writing errors in sentence structure which includes four aspects. Based on the findings, it proves that the factors causing language errors in students' essays are due to less attention to the use of grammar in writing, the lack of vocabulary owned by students, and teachers pay less attention and provide sentence writing exercises.